A pair of bubbles' rising dynamics in a xanthan gum solution: a CFD study - Islam, M.T.; Ganesan, P.; Cheng, J. (Royal Society of Chemistry, 2015)
The motion and interaction of a bubble pair in a non-Newtonian fluid (xanthan gum solution) were numerically simulated using a volume of fluid (VOF) method, in which the continuous surface tension model and the power-law model were adopted to represent the surface tension and rheological properties of non-Newtonian fluids, respectively. The effects of the initial horizontal bubble interval, oblique alignment and rheological properties of non-Newtonian fluids on a pair of bubbles rising side-by-side are evaluated in this study. The results indicate that for the case with a non-dimensional initial horizontal bubble interval h* = 4.0, the interaction between the bubbles shows a minimal repulsive effect. Moreover, for the oblique angle alignment a greater repulsive force between the bubbles was seen when the angle was reduced. However, oblique coalescence occurred due to the higher attraction between the bubbles at higher angles, which is independent of the flow index. It is also found that the repulsion effect as well as the variation of the bubble shape from spherical to irregular are more significant at a lower flow index (n < 0.5) due to the shear-thinning effect as well as the differences in their flow field structures.